Parenting a child with congenital cytomegalovirus infection: a qualitative study. Issue 1 (12th November 2020) - Vandrevala, Tushna; Barber, Victoria; Mbire-Chigumba, Evas; Calvert, Anna; Star, Caroline; Khalil, Asma; Griffiths, Paul; Book, Alexander S; Book, Gayle M; Heath, Paul; Jones, Christine E
Abstract : Background: Congenital cytomegalovirus (CMV) is the most common infectious cause of congenital disability, which can cause lifelong impairments including sensorineural hearing loss and developmental delay. This study aimed to explore the experiences of parenting a child with congenital CMV and the impact this has on families. Methods: Ten parents living with a child with congenital CMV in the UK participated in semistructured interviews and data were analysed using thematic analysis. Results: The findings illustrate that delays in making the diagnosis of congenital CMV are associated with parental distress and lack of knowledge about CMV among medical professionals can exacerbate this distress. Parents expressed frustration about not knowing about CMV infection during their pregnancies and therefore not having the opportunity to take measures to reduce their risk of acquiring CMV while pregnant. The uncertainty about the long-term outcomes of children with congenital CMV adds additional emotional burden for parents. Family and wider societal networks have the potential to facilitate coping and alleviate stress, but the lack of awareness of CMV acts as a barrier to receiving support from family and friends. Conclusions: There is a need to increase awareness of CMV among medical professionals, pregnant women and wider society to improve the diagnostic process and to provide better support for families caring for children with congenital CMV infection.